2022
DOI: 10.1155/2022/6125698
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Noncoding RNA in Airway Allergic Diseases through Regulation of T Cell Subsets

Abstract: Allergic rhinitis and asthma are common airway allergic diseases, the incidence of which has increased annually in recent years. The human body is frequently exposed to allergens and environmental irritants that trigger immune and inflammatory responses, resulting in altered gene expression. Mounting evidence suggested that epigenetic alterations were strongly associated with the progression and severity of allergic diseases. Noncoding RNAs (ncRNAs) are a class of transcribed RNA molecules that cannot be trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 186 publications
0
3
0
Order By: Relevance
“…LncRNA can regulate immune cell differentiation by interacting with transcription factors, participate in the expression of inflammatory factors in immune response and control inflammatory response. 34 At present, the role of circRNA in the pathogenesis of AR has not been clearly reported.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…LncRNA can regulate immune cell differentiation by interacting with transcription factors, participate in the expression of inflammatory factors in immune response and control inflammatory response. 34 At present, the role of circRNA in the pathogenesis of AR has not been clearly reported.…”
Section: Discussionmentioning
confidence: 98%
“…The miRNA and lncRNA almost participate in the whole process of AR pathogenesis and persistence, including the injury reaction of nasal epithelial cells, antigen presentation of dendritic cells, differentiation and activation of T helper cells, development and recruitment of eosinophils, and degranulation of mast cells in the early stage. 34 Studies have shown that 35 miR-126 may be involved in the pathogenesis of AR by positively regulating the expression of Treg cytokines and negatively regulating the expression of the Th1 and Th2 cytokines. It can be inferred that these miRNAs also play a key role in AR.…”
Section: Discussionmentioning
confidence: 99%
“…ZNF667-AS1 is classified as a long-stranded non-coding RNA (lncRNA) with multifaceted activities. lncRNAs were proven to play an integral role in the pathogenesis of allergic disease by regulating the differentiation and apoptosis of hematopoietic stem cells, bone marrow cells, and the activation of monocytes, macrophages, and dendritic cells in immune regulation ( Cheng et al, 2022 ). ZNF667-AS1 has been the focus of recent research on inflammatory conditions and cancer with an emphasis on its function in the control of inflammatory pathways ( Di Fiore et al, 2021 ; Zheng et al, 2021 ; Fan et al, 2022 ; Luan et al, 2022 ; Ma et al, 2022 ; Bohosova et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%